2021
DOI: 10.1016/j.heliyon.2021.e07162
|View full text |Cite
|
Sign up to set email alerts
|

Climate change adaptation strategies by smallholder farmers in Nigeria: does non-farm employment play any role?

Abstract: Non-farm employment in agrarian communities in developing countries has received a lot of attention. However, its role in implementing climate change adaptation strategies is rarely discussed. This study employs a crosssectional data to examine whether rural households in Southwest Nigeria are increasing the extent of climate change adaptation practices through their participation in non-farm employment. To account for selectivity bias, the study used endogenous treatment effect for count data model (precisely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 76 publications
4
13
0
Order By: Relevance
“…Approaches based on propensity scores, such as regression adjustment, propensity score matching and inverse probability weighting, solely account for observed heterogeneity, whereas IV methods account for both observed and undiscovered heterogeneity. Danso-Abbeam et al (2021) employed the instrumental variable Poisson regression model, which was also used in this study. The model estimates the causal effect of market participation on nutrition security status using the count outcome with a Poisson distribution of the error term.…”
Section: Discussionmentioning
confidence: 99%
“…Approaches based on propensity scores, such as regression adjustment, propensity score matching and inverse probability weighting, solely account for observed heterogeneity, whereas IV methods account for both observed and undiscovered heterogeneity. Danso-Abbeam et al (2021) employed the instrumental variable Poisson regression model, which was also used in this study. The model estimates the causal effect of market participation on nutrition security status using the count outcome with a Poisson distribution of the error term.…”
Section: Discussionmentioning
confidence: 99%
“…It is in the northern part of the country and spans across several other states, including Kebbi, Sokoto, Zamfara, Katsina, Kano, Jigawa, Bauchi, Gombe, Yobe, Borno, Taraba, Adamawa, and parts of Niger and Benue states. Te zone experiences a semiarid climate, characterized by a distinct wet and dry season [36,37]. Te wet season typically lasts from May to October, during which the region receives average annual rainfall ranging from 800 mm to 1200 mm, supporting the growth of grasses, shrubs, and scattered trees [37,38].…”
Section: Study Areamentioning
confidence: 99%
“…Te zone experiences a semiarid climate, characterized by a distinct wet and dry season [36,37]. Te wet season typically lasts from May to October, during which the region receives average annual rainfall ranging from 800 mm to 1200 mm, supporting the growth of grasses, shrubs, and scattered trees [37,38]. Tese vegetation types form the characteristic savanna landscape, consisting of a mix of tall grasses, baobab trees, acacias, and shea trees [37].…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Maize crops survive between 160 o C and 190 o C and consistently require a specific amount of precipitation (Adeagbo et al, 2021). While farmers are aware of the impacts of climate change on their farming activities (Adebayo et al, 2013), studies (Stringer et al2020;Ojo and Baiyegunhi, 2020;Danson-Abbeam et al, 2021) have shown that rural farmers are adapting to climate change through various measures. Climate change adaptation is especially important in developing countries since these countries are predicted to bear the brunt of the effects of climate change (Omerkhil et al, 2020).…”
Section: Introductionmentioning
confidence: 99%